Human singularity. Mind. Spirit. (Three Big Questions) - Rolston, Holmes, 1932-2025, speaker; Viney, Wayne, speaker; Dik, Bryan, speaker (Colorado State University. Libraries, 2012)
Humans on Earth are a singularity beyond animal achievements, considering genetics, neuroscience, moral, psychological, philosophical, and spiritual experience. This gives humans a unique dignity. Science has been discovering deep space, deep time, and pushing deep down into subatomic nature. On astronomical scales, we are cosmic dwarfs. But another perspective is possible: If we ask where the "deep" thoughts about this "deep" nature are, they are right here. Such thoughts are scientific, they are also philosophical and religious. We alone can ask big questions.
With commentary by Wayne Viney and Bryan Dik. Recorded April 26, 2012. Disk 1, Lecture, 44 minutes. Disk 2, Discussion, 54 minutes.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.